Percutaneous Coronary Intervention for Vulnerable Coronary Atherosclerotic Plaque - Stone, Gregg W; Maehara, Akiko; Ali, Ziad A; Held, Claes; Matsumura, Mitsuaki; Kjøller-Hansen, Lars; Bøtker, Hans Erik; Maeng, Michael; Engstrøm, Thomas; Wiseth, Rune; Persson, Jonas; Trovik, Thor; et al. (Journal of the American College of Cardiology, 2020)
Acute coronary syndromes most commonly arise from thrombosis of lipid-rich coronary atheromas that have large plaque burden despite angiographically appearing mild. This study sought to examine the outcomes of percutaneous coronary intervention (PCI) of non-flow-limiting vulnerable plaques. Three-vessel imaging was performed with a combination intravascular ultrasound (IVUS) and near-infrared spectroscopy (NIRS) catheter after successful PCI of all flow-limiting coronary lesions in 898 patients presenting with myocardial infarction (MI). Patients with an angiographically nonobstructive stenosis not intended for PCI but with IVUS plaque burden of ≥65% were randomized to treatment of the lesion with a bioresorbable vascular scaffold (BVS) plus guideline-directed medical therapy (GDMT) versus GDMT alone. The primary powered effectiveness endpoint was the IVUS-derived minimum lumen area (MLA) at protocol-driven 25-month follow-up. The primary (nonpowered) safety endpoint was randomized target lesion failure (cardiac death, target vessel-related MI, or clinically driven target lesion revascularization) at 24 months. The secondary (nonpowered) clinical effectiveness endpoint was randomized lesion-related major adverse cardiac events (cardiac death, MI, unstable angina, or progressive angina) at latest follow-up. A total of 182 patients were randomized (93 BVS, 89 GDMT alone) at 15 centers. The median angiographic diameter stenosis of the randomized lesions was 41.6%; by near-infrared spectroscopy-IVUS, the median plaque burden was 73.7%, the median MLA was 2.9 mm , and the median maximum lipid plaque content was 33.4%. Angiographic follow-up at 25 months was completed in 167 patients (91.8%), and the median clinical follow-up was 4.1 years. The follow-up MLA in BVS-treated lesions was 6.9 ± 2.6 mm compared with 3.0 ± 1.0 mm in GDMT alone-treated lesions (least square means difference: 3.9 mm ; 95% confidence interval: 3.3 to 4.5; p < 0.0001). Target lesion failure at 24 months occurred in similar rates of BVS-treated and GDMT alone-treated patients (4.3% vs. 4.5%; p = 0.96). Randomized lesion-related major adverse cardiac events occurred in 4.3% of BVS-treated patients versus 10.7% of GDMT alone-treated patients (odds ratio: 0.38; 95% confidence interval: 0.11 to 1.28; p = 0.12). PCI of angiographically mild lesions with large plaque burden was safe, substantially enlarged the follow-up MLA, and was associated with favorable long-term clinical outcomes, warranting the performance of an adequately powered randomized trial. (PROSPECT ABSORB [Providing Regional Observations to Study Predictors of Events in the Coronary Tree II Combined with a Randomized, Controlled, Intervention Trial]; NCT02171065).